BRAFV600E Kinase Domain Duplication Identified in Therapy-Refractory Melanoma Patient-Derived Xenografts - Kristel Kemper; Oscar Krijgsman; Xiangjun Kong; Paulien Cornelissen-Steijger; Aida Shahrabi; Fleur Weeber; Daphne L. van der Velden; Onno B. Bleijerveld; Thomas Kuilman; Roel J.C. Kluin; Chong Sun; Emile E. Voest; et al. (Cell Reports, 2016)
The therapeutic landscape of melanoma is improving rapidly. Targeted inhibitors show promising results, but drug resistance often limits durable clinical responses. There is a need for in vivo systems that allow for mechanistic drug resistance studies and (combinatorial) treatment optimization. Therefore, we established a large collection of patient-derived xenografts (PDXs), derived from BRAFV600E, NRASQ61, or BRAFWT/NRASWT melanoma metastases prior to treatment with BRAF inhibitor and after resistance had occurred. Taking advantage of PDXs as a limitless source, we screened tumor lysates for resistance mechanisms. We identified a BRAFV600E protein harboring a kinase domain duplication (BRAFV600E/DK) in ∼10% of the cases, both in PDXs and in an independent patient cohort. While BRAFV600E/DK depletion restored sensitivity to BRAF inhibition, a pan-RAF dimerization inhibitor effectively eliminated BRAFV600E/DK-expressing cells. These results illustrate the utility of this PDX platform and warrant clinical validation of BRAF dimerization inhibitors for this group of melanoma patients.